2022
DOI: 10.1111/bcp.15432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association of anticholinergic burden and delirium in older hospitalised patients – A cohort study comparing 19 anticholinergic burden scales

Abstract: A recent review identified 19 anticholinergic burden scales (ABSs) but no study has yet compared the impact of all 19 ABSs on delirium. We evaluated whether a high anticholinergic burden as classified by each ABS is associated with incident delirium. Method:We performed a retrospective cohort study in a Swiss tertiary teaching hospital using data from 2015-2018. Included were patients aged ≥65, hospitalised ≥48 hours with no stay >24 hours in intensive care. Delirium was defined twofold:(i) ICD-10 or CAM and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…We replicated the lack of association between cognitive impairment in bipolar patients and Anticholinergic Drug Scale values reported by Eum et al (2017). Previous use of Chew's scale showed its association with cognitive impairment in elderly patients (Lampela et al, 2013;Lisibach et al, 2021), whereas the Anticholinergic Toxicity Scale has been shown to be strongly associated with delirium and mortality in elderly patients (Lisibach et al, 2022a(Lisibach et al, & 2022b, but no study has explored their association with cognitive performance for individuals with psychiatric disorders. Indeed, Chew's scale was designed based exclusively on in vitro measures of serum anticholinergic activity and the Anticholinergic Toxicity Scale was designed based on the affinity for muscarinic receptors deduced from the molecular structure of the drug: neither of the two scales were designed based on clinical observations, making our results quite unexpected.…”
Section: Discussionsupporting
confidence: 72%
“…We replicated the lack of association between cognitive impairment in bipolar patients and Anticholinergic Drug Scale values reported by Eum et al (2017). Previous use of Chew's scale showed its association with cognitive impairment in elderly patients (Lampela et al, 2013;Lisibach et al, 2021), whereas the Anticholinergic Toxicity Scale has been shown to be strongly associated with delirium and mortality in elderly patients (Lisibach et al, 2022a(Lisibach et al, & 2022b, but no study has explored their association with cognitive performance for individuals with psychiatric disorders. Indeed, Chew's scale was designed based exclusively on in vitro measures of serum anticholinergic activity and the Anticholinergic Toxicity Scale was designed based on the affinity for muscarinic receptors deduced from the molecular structure of the drug: neither of the two scales were designed based on clinical observations, making our results quite unexpected.…”
Section: Discussionsupporting
confidence: 72%
“…We replicated the lack of association between cognitive impairment in bipolar patients and Anticholinergic Drug Scale values reported by Eum et al (2017) . Previous use of Chew's scale showed its association with cognitive impairment in elderly patients ( Lampela et al, 2013 ;Lisibach et al, 2021 ), whereas the Anticholinergic Toxicity Scale has been shown to be strongly associated with delirium and mortality in elderly patients ( Lisibach et al, 2022a( Lisibach et al, & 2022b, but no study has explored their association with cognitive performance for individuals with psychiatric disorders. Indeed, Chew's scale was designed based exclusively on in vitro measures of serum anticholinergic activity, and the Anticholinergic Toxicity Scale was designed based on the affinity for muscarinic receptors deduced from the molecular structure of the drug: neither of the two scales was designed based on clinical observations, making our results quite unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a delirium occurrence of 11%, which is at the lower end of the range found in the literature [ 1 ]. Although the DOSS is not considered to be a standard diagnostic tool, unlike the CAM, we included the DOSS in our delirium definition based on a previous sensitivity analysis [ 7 ], which did not show major differences in the effect size between the DOSS and the CAM. Additionally, including the DOSS might address the previously reported problem of delirium underdiagnosing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The years 2015/2016 were used for development and 2017/2018 for external validation. The cohort selection criteria, outcome definition and predictors are summarised below and have been described elsewhere in more detail [ 7 ]. This study was undertaken per the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) statement [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation